(untitled) (Journal of Parents and Teachers, 2013)
Theoretical developments of physics and astronomical observations have led to the present image of an universe in evolution. This image is included in the big-bang standard model. The general lines of this model are its spatial and temporal origin about 13700 million years ago, and its spatial expansion and cooling and the evolution from elementary particles to system of increasing complexity. Christian faith affirm the divine creation as ontological cause if its existence. Both points of view are not incompatible and between them there must exists a dialogue.